Environmental effects of maritime traffic on the &Aumlaut°stanbul Strait - Birpinar, Mehmet E.; Talu, Gonca F.; Gonencgil, Barbaros (SPRINGER, 2009)
The &Aumlaut degrees stanbul Strait, which separates the European and the Asian parts of &Aumlaut degrees stanbul, is one of the narrowest straits in the world that is used for international shipping. The Strait has very special ecological conditions in terms of marine environment (atmospheric/oceanographic conditions, plant and animal diversity) and terrestrial environment. It also has roles as biological corridor and biological barrier between the Mediterranean Sea and the Black Sea and form an acclimatization zone for migrating species. Due to being the only maritime access for the neighboring Black Sea states and the Central Asian Turki Republics, the &Aumlaut degrees stanbul Strait has been exposed to dense marine traffic for centuries and substantial increase has occurred in size and tonnage of the ships passing through the Strait with hazardous cargo varieties and amounts they carry. Increase in the number of vessels that navigates on the Strait and being on the transportation way of hazardous and dangerous materials pose serious environmental and safety hazards for the &Aumlaut degrees stanbul Strait, Marmara Sea and the surrounding residential areas. Geographic and oceanographic features of the &Aumlaut degrees stanbul Strait makes the navigation on the Strait rather difficult and consequently the Strait has faced many casualties that caused severe environmental problems due to thousands tons of oil spill occurring in recent decades.
Keywords: The Istanbul Strait; Bosphorus; Maritime traffic; Maritime casualties; Oil pollution; CASUALTIES; BOSPORUS; Environmental Sciences & Ecology